Prophylactic Edaravone Prevents Transient Hypoxic-Ischemic Brain Injury: Implications for Perioperative Neuroprotection - Sun, Yu-Yo (Stroke, 2015)
BACKGROUND AND PURPOSE: Hypoperfusion-induced thrombosis is an important mechanism for post-surgery stroke and cognitive decline, but there are no perioperative neuroprotectants to date. This study investigated whether prophylactic application of Edaravone, a free radical scavenger already used in treating ischemic stroke in Japan, can prevent infarct and cognitive deficits in a murine model of transient cerebral hypoxia-ischemia. METHODS: Adult male C57BL/6 mice were subjected to transient hypoxic-ischemic (tHI) insult that consists of 30-min occlusion of the unilateral common carotid artery and exposure to 7.5% oxygen. Edaravone or saline was prophylactically applied to compare their effects on cortical oxygen saturation, blood flow, coagulation, oxidative stress, metabolites, and learning-memory using methods that include photoacoustic imaging, laser speckle contrast imaging, solid state NMR and Morris water maze. The effects on infarct size by Edaravone application at different time-points after tHI were also compared. RESULTS: Prophylactic administration of Edaravone (4.5 mg/kg × 2, IP, 1 h before and 1 h after tHI) improved vascular reperfusion, oxygen saturation, and the maintenance of brain metabolites, while reducing oxidative stress, thrombosis, white-matter injury, and learning impairment after tHI insult. Delayed Edaravone treatment after 3 h post-tHI became unable to reduce infarct size. CONCLUSIONS: Acute application of Edaravone may be a useful strategy to prevent post-surgery stroke and cognitive impairment, especially in patients with severe carotid stenosis.